Los enigmáticos capuchinos - Di Giacomo, Adrián; Kopuchian, Cecilia; Campagna, Leonardo (Revista Aves Argentinas, 2023)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).